Representasi nilai moral yang terkandung dalam film Kabayarammi Cinnaku karya Prof. Dr. Hj. Kembong daeng, M.Hum.: Representation of moral values ​​contained in the film Kabayarammi Cinnaku by Prof. Dr. Hj. Kembong Daeng, M.Hum. - Agustina, Nur Widya; Hajrah, Hajrah; Yunus, Andi Fatimah (Journal Studies in Indonesian Language and Literature, 2025)
"Representation of Moral Values Contained in the Film Kabayarammi Cinnaku karya Prof. Dr. Hj. Kembong Daeng, M.Hum”. Thesis, Department of Indonesian Language and Literature, Faculty of Language and Literature, Makassar State University. Supervised by Hajrah and Andi Fatimah Yunus.In this study, the researcher took the film Kabayarammi Cinnakku by Prof. Hj.Kembong Daeng, M.Hum. as the subject of the study. The purpose of this study is to describe the moral values contained in the film Kabayarammi Cinnaku by Prof. Dr. Hj. Kembong Daeng, M.Hum., using the theory of moral values, in the study using observation techniques and document studies. This type of research is qualitative research. The purpose of this qualitative research is to obtain information about the state of the existing research object. The results of this research show that there is a representation of moral values contained in the film Kabayarammi Cinnaku by Prof. Dr. Hj. Kembong Daeng, M. Hum. namely the moral values contained in the relationship between humans and themselves, namely never giving up, responsibility and perseverance, the moral values contained in the relationships between humans and fellow humans, including helping each other and respecting each other, and the moral values contained in the relationship between humans and God include gratitude, prayer, trust, patience and honesty.